Análise de falha aplicada em um motor de empilhadeira de cargas - COELHO, Andressa da Silva (2022)
The mining activity in Brazil has a significant participation in the country's economic development, currently Brazil has the largest open pit iron mine in the world. In the mining field, auxiliary equipment is used to optimize the maintenance, production, and cargo handling activities. However, failures that occur in this auxiliary equipment end up directly affecting the availability of assets. In addition make the maintenance and putting the equipment in a state that can perform its required functions, it is necessary to carry out the treatment of these failures and propose actions to block their recurrence. The present work consists of a technical investigation of the motivating causes of the failure of a diesel engine of a forklift used in cargo handling activities in a heavy equipment maintenance workshop. To identify the root cause, quality tools such as the Five Whys and Ishikawa Diagram will be used. The use of these tools allows the maintenance engineer to eliminate unlikely causes, and separate effects from causes, conceiving a robust, informed and assertive analysis. After identifying the primary cause of the failure, actions will be proposed to reduce or mitigate the probability of recurrence of the event, allowing the equipment to operate with greater reliability and availability.